Mycobacterium chimaera infections: An update. Issue 3 (March 2020) - Riccardi, Niccolò; Monticelli, Jacopo; Antonello, Roberta Maria; Luzzati, Roberto; Gabrielli, Marco; Ferrarese, Maurizio; Codecasa, Luigi; Di Bella, Stefano; Giacobbe, Daniele Roberto
Abstract: Mycobacterium chimaera is a non-tuberculous mycobacterium belonging to the Mycobacterium avium complex, described for the first time in 2004. It acts as an opportunistic pathogen, with infections, usually respiratory illnesses, occurring more frequently in immunocompromised patients or in patients with underlying respiratory diseases. During the last decade Mycobacterium chimaera disseminated infections following cardiothoracic surgery, especially open-heart surgery, have been increasingly reported worldwide. From a pathogenic standpoint, Mycobacterium chimaera is acquired during cardiopulmonary bypass via bioaerosols emitted from contaminated heater-cooler units water systems. Due to non-specific symptoms and long latency, postoperative Mycobacterium chimaera infections may not be promptly diagnosed and treated, and may become life-threatening. The indication for revision surgery needs to be carefully evaluated on a case-by-case basis, and antibiotic therapy should be based on drug susceptibility testing results. Our review aims to provide an updated account of microbiological characteristics, clinical presentation, diagnosis, and management of Mycobacterium chimaera infections, with a special focus on those developing after cardiothoracic surgery.